Diagnostischer Irrtum: Tun und Unterlassen und strafrechtliche Sorgfaltsbestimmung bei der ärztlichen Diagnosestellung - Spyropoulos, Ilias (Tectum Verlag, 2023)
This work is a study in medical criminal law that deals with medical malpractice in the narrower sense and, in particular, with medical diagnostic errors. The author starts from a conceptual definition of diagnostic error under medical criminal law and examines its relevance for the controversial question of the demarcation between doing and omitting to do a diagnosis. He also aims to determine the due diligence requirements under criminal law with regard to medical diagnosis on the basis of negligence theories, medical guidelines and ultimately with the help of case law.